2020
DOI: 10.1002/bsl.2481
|View full text |Cite
|
Sign up to set email alerts
|

Rising inpatient numbers in forensic security hospitals of German federal state of Baden‐Württemberg: Background and explanatory approaches

Abstract: In this article, we describe critical epidemiological trends in forensic psychiatric care in the German federal state of Baden-Württemberg. For some years, there has been a marked increase in the number of patients with psychoses and with a migration background in the high-security hospitals of Baden-Württemberg. We present a number of studies exploring hypotheses as to why this is the case. Taking into account a set of person-related and non-person (forensic system)-related variables, we suggest that rising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…That said, all inpatients meet the criteria for a mental disorder, as this is a requirement for admission to a forensic hospital under the German Criminal Code. A recent study across forensic hospitals in the German federal state of Baden-Württemberg found that schizophrenia spectrum disorders, personality disorders, and substance abuse disorders are among the most common diagnoses [ 78 ]. Consequently, treatment plays a crucial role in these facilities, with the Reichenau Centre of Psychiatry implementing psychotherapy through both individual and group sessions several times a week, which is further complemented by pharmacotherapeutic interventions.…”
Section: Methodsmentioning
confidence: 99%
“…That said, all inpatients meet the criteria for a mental disorder, as this is a requirement for admission to a forensic hospital under the German Criminal Code. A recent study across forensic hospitals in the German federal state of Baden-Württemberg found that schizophrenia spectrum disorders, personality disorders, and substance abuse disorders are among the most common diagnoses [ 78 ]. Consequently, treatment plays a crucial role in these facilities, with the Reichenau Centre of Psychiatry implementing psychotherapy through both individual and group sessions several times a week, which is further complemented by pharmacotherapeutic interventions.…”
Section: Methodsmentioning
confidence: 99%
“…German forensic psychiatric units house mentally ill forensic patients (Section 63 of the German Penal Code) (21) suffering from schizophrenia, personality disorder or intelligence reduction (23) as well as substance-dependent patients (Section 64 of the German Penal Code) (21) who are dependent on alcohol or drugs (23). In addition to the psychiatric clinical pictures and comorbidities, patients also exhibit sociopsychological deficits (23).…”
Section: Sample and Recruitmentmentioning
confidence: 99%
“…The closure of mental health beds was accompanied by an increase in referrals from prison to hospital for treatment (civil or forensic involuntary detentions). Convincing evidence of long-term significant increases in placements in forensic psychiatric facilities is also available from Germany ( 10 13 ).…”
Section: Introduction: International Trends On Forensic Mental Health...mentioning
confidence: 99%